Karakteristik pasien diabetes melitus tipe 2 dengan tinea korporis di SMF Ilmu Kesehatan Kulit dan Kelamin RSUP. Haji Adam Malik Medan periode tahun 2010-2012 - Ade Sri Wahyuni; Meidina K. Wardani; Isma Aprita Lubis (Majalah Kedokteran Nusantara The Journal Of Medical School, 2013)
Introduction : Tinea corporis is one of the manifestations of skin disorders due to complications of type 2 diabetes mellitus (DM). Complications of diabetes on the skin commonly aggravated by high blood sugar levels which can increase susceptibility to infection. Complications associated with glycemic control.To determine the characteristics of type 2 diabetes melitus patients with tinea corporis in the Department of Dermatology and Venereology in Haji Adam Malik General Hospital period of January 2010-Desember 2012.Methods : The study was a descriptive study, which was conducted retrospectively using secondary data from the medical record type 2 diabetes mellitus patients with tinea corporis who came for treatment to the Department of Dermatology and Venereology in Haji Adam Malik General Hospital period of January 2010-Desember 2012.Results : The number of type 2 diabetes melitus patients with tinea corporis which visited the Department of Dermatology and Venereology in Haji Adam Malik General Hospital period of January 2010-Desember 2012 was 47 people. The characteristic of type 2 DM patients with tinea corporis was commonly female (70.2%), mostly between the age of 61-70 (48.90%), mostly the education level was senior high school (36.2%), the most common occupation was housewive (40.4%), based on the duration of the type 2 DM disease, the most commonly found was less than 5 years (53.2%), the glycemic control most commonly was with the uncontrolled HbA1c level or having the HbA1c level greater than 7 (78.7%).Conclusion: The characteristics of type 2 diabetes melitus patients with tinea corporis which visited the Department of Dermatology and Venereology in Haji Adam Malik General Hospital period of January 2010-Desember 2012 was 47 people of the patients were commonly female, between the age of 61-70, the highest education level was senior high school, the accupation was housewive, the duration of the type 2 DM disease was less than 5 years and the glycemic control mostly were with uncontrolled HbA1c level or having the HbA1c level greater than 7.Keywords : diabetes mellitus type 2; tinea corporis; characteristics